The Implementation of Artificial Intelligence in Developing English Language Teaching Material: Case Study of English Teachers at SMP IT Mantab in Sabak Auh, Siak Sri Indrapura - Ati Adzki Fikria; Sutarmo, Sutarmo; Bukhori, Bukhori (CV. ULIL ALBAB CORP, 2025)
The present study investigates the implementation of Artificial Intelligence (AI) in developing English language teaching materials by two English teachers at SMP IT Mantab in Sabak Auh, Siak Sri Indrapura. Using a qualitative case study method, the research highlights the teachers’ perceptions, the types of AI tools used, and their strategies for adapting AI-generated content for classroom use. The findings reveal that teachers used AI tools such as ChatGPT, QuillBot, and Canva to enhance the relevance, accuracy, and creativity of th eir instructional materials. While the tools facilitated content generation and lesson planning, challenges remained in evaluating AI-generated material and ensuring its alignment with curriculum goals. This study provides valuable insights into AI integration at the classroom level, with implications for educators, school leadership, and future research.